1959
DOI: 10.1063/1.1730126
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Adsorption Characteristics of Clean Surfaces of Germanium and Silicon

Abstract: Diffraction patterns obtained from atomically clean germanium surfaces contained half-integral order beams in (110) azimuths for both (100) and (110) surfaces and in all azimuths for the (111) surface. These results are considered to be due to displacements of surface atoms from their normal bulk lattice positions in the surface plane. Adsorption of oxygen on all of these surfaces extinguished all of the diffraction beams which were not integral order.In addition to the normal surface lattice spacings of clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
151
0
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 878 publications
(164 citation statements)
references
References 12 publications
7
151
0
3
Order By: Relevance
“…[5][6][7] Surfaces such as the Ge(001)-(2 Â 1) reconstructed surface and the MoO 2 /Mo(110) surface exhibit well-defined nanorows formed by Ge dimers and Mo oxide, respectively. 8,9 Such surfaces are suitable templates for the growth of well-ordered, uniformly sized metal nanoclusters. 10,11 In the present work we use the Ge(001)-(2 Â 1) reconstructed surface and the MoO 2 /Mo(110) surface as templates for the growth of ordered arrays of Fe nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Surfaces such as the Ge(001)-(2 Â 1) reconstructed surface and the MoO 2 /Mo(110) surface exhibit well-defined nanorows formed by Ge dimers and Mo oxide, respectively. 8,9 Such surfaces are suitable templates for the growth of well-ordered, uniformly sized metal nanoclusters. 10,11 In the present work we use the Ge(001)-(2 Â 1) reconstructed surface and the MoO 2 /Mo(110) surface as templates for the growth of ordered arrays of Fe nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…1 Fundamental interest has been focused on (1) the bonding of atomic species with the highly directional surface dangling bonds, 2 and (2) surface restructuring induced by the adsorbate. 3 In chemisorption, the surface trades off energy lost by local bond formation with energy gained by elastic distortion of substrate atoms in search of the lowest free energy bonding configuration.…”
mentioning
confidence: 99%
“…9 Spectroscopy and STM experiments suggested that the most stable configuration of silicon (100) surface around 100 K is the c(4 × 2) arrangement in buckled structure. [10][11][12][13] In 2000, however, the STM and AFM measurements indicated the p(2 × 1) symmetric image below 80 K. 6,[14][15][16] Also, LEED measurements below 40 K reported the same structural a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%